BAHASA PERSUASIF PADA TEKS KATOBBA PALLAPPASSANG ‘KHOTBAH LEBARAN’ DI KABUPATEN GOWA - Saputra, Muh Ali; Daeng, Kembong; Yunus, Andi Fatimah (Journal of Applied Linguistics and Literature, 2024)
This research aims to describe the form of persuasive language in the text of katobba pallappassang 'Eid sermon' in Gowa Regency, and revealing persuasive techniques in the text of the katobba pallapassang 'Eid sermon' in Gowa Regency. The method was designed using descriptive qualitative research. The data in this study comes from 2 texts of katobba pallappassang 'Eid sermon', 1 text katobba pallappassang rumallang 'Eid al-Fitr sermon', and 1 text of the katobba pallappassang hajj 'Eid al-Adha sermon' obtained from a religious figure named Muh. Ramli, S.Pd.I., Dg. Laja. Data collection was carried out using copy, read and note techniques. The results of the research show that, (1) 4 applications of persuasive form were found, namely persuasive form of invitation, persuasive form of affirmation, persuasive form of advice, and persuasive form of prohibition. (2) 4 applications of persuasive techniques were found, namely association persuasive techniques, integration persuasive techniques, pay off & fear arousing persuasive techniques, and icing persuasive techniques. The application of persuasive forms and techniques is carried out to influence the communicant or congregation so that the desired persuasion goals can be achieved.